The Battle of Kursk - Glantz, David M. 1942- (Modern war studies, 1999)
"Immense in scope, ferocious in nature, and epic in consequence, the Battle of Kursk witnessed (at Prokhorovka) one of the largest tank engagements in world history and led to staggering losses - including nearly 200,000 Soviet and 50,000 German casualties - within the first ten days of fighting. Going well beyond all previous accounts, David Glantz and Jonathan House now offer the definitive work on arguably the greatest battle of World War II."--BOOK JACKET.